Teoria e ensino de história na Espanha : as prescrições de Ignácio Ramón Miró y Manent (1855-1889) - Santos, Analice Alves Marinho (2018)
This dissertation analysis the relation Theory of History versus Teaching of History problematizing the appropriations of the critical method developed by Spanish historian Ignacio Ramón Miró y Manent (1821-1892). In the second half of the nineteenth century, Miró y Manent proposed a patriotic and Christian teaching of history for Spanish schools. Drawing upon Laurence Bardin’s analysis of content technic (1977), we were able to identify the intents and methodology Miró y Manent recommended to the discipline of history. Thereafter, we analyzed how the author associated the teaching of history to the formation of individuals for an ideal type of nation: a Spain that was catholic, unified, and unique. This study claims that Miró y Manent presented two conceptions of History: one for school teaching and other for universities. In his opinion, the teaching of history in schools presented an excess of disconnected information uninteresting to students. As a solution, the Spanish historian proposed a teaching of history focused on the development of skills to understanding important facts of the Spanish experience (teacher’s role), the comprehension of facts, and connection between causes and consequences (student’s role). Nevertheless, Miró y Manent’s proposals present contradictions between his understanding of Theory of History and his suggestions for basic education. Furthermore, his scholarship evidences some nostalgia in a moment when Spain was leaving behind political and religious conservative ideals in the late nineteenth century.